Interventional Strategies to Mitigate Maternal Stress and Enhance Coping Skills During Neonatal Admission Into Intensive Care Units in Low‐ and Middle‐Income Countries: A Scoping Review - N. Siva; Binil Velayudhan; Baby S. Nayak; Leslie Edward S. Lewis; Faiza Iqbal; Judith Angelitta Noronha (Wiley, 2024)
ABSTRACT Background Mothers of high‐risk neonates experience tremendous stress during neonatal intensive care unit (NICU) admission. This stress has a negative impact on mothers' participation in neonatal care activities, psychological health and coping skills in the NICU. Objective To determine the impact of interventional strategies to reduce maternal stress and enhance coping skills during neonatal admission to the NICU. Design A scoping review was carried out following the methodological framework outlined by Arksey and O'Malley. Methods This scoping review was conducted as per the Joanna Briggs Institute guidelines, including a quality appraisal checklist for randomised and nonrandomised controlled trials. Patterns, advances, gaps, evidence for practice and research recommendations from the review (PAGER framework) were used to report the results. The following international databases were used to search for primary articles: Medline via PubMed, EBSCOhost via CINAHL, Scopus, Web of Science and the ProQuest Medical Library. Original studies published in English between January 2011 and January 2023 from low‐ and middle‐income countries (LMICs) that assessed maternal stress and coping skills during neonatal NICU admission were included in the review. Results The review included 15 articles from LMICs, of which 60% were from middle‐income, 25% were from lower‐middle‐income and 15% were from low‐income countries. Interventional strategies were described under five categories. Maternal stress decreased significantly across all three subscales of the PSPS: 'sight and sound', 'baby looks and behavior' and 'parental relationship with baby and role alteration' during neonatal NICU admission. Interventional strategies involving family‐centred care and emotional and psychological supportive care have been reported to have a consistently positive impact on alleviating maternal stress and enhancing coping skills in the NICU. Conclusion Healthcare professionals, especially nurses, are pivotal in promptly recognising maternal stress and NICU stressors. The participation of mothers in neonatal care, such as through family‐centred care and emotional support interventions, significantly reduces maternal stress and enhances coping skills.